Peningkatan Kompetensi Pembuatan Media Presentasi Interaktif Berbasis Teknologi Digital (Canva) Bagi Mahasiswa Kesehatan Masyarakat - Putri Utami (Yayasan Literasi Sains Indonesia, 2025)
In the current era of digital technology development, it is necessary for students to be able to present assignments in the form of paper results into effective, attractive and interactive visual displays. This is useful for conveying information to the audience, both fellow classmates and the general public. However, often the habit of students in making presentation media only contains copies of paper writing to presentation slides so that the presentation display is full of writing without making certain points, other habits are using font sizes that are too small, choosing slide designs that are not appropriate for presenting presentations in a formal atmosphere, and so on, even though interesting and interactive presentations play an important role in the absorption of information to the audience. The purpose of this training is to conduct training on making good presentation media for students. The method of implementing this activity is divided into three stages, namely the preparation stage, training implementation and evaluation. The targets of the training were 53 first semester students from the S1 Public Health Study Program. The success of the training can be seen from the improvement in students' knowledge and skills in creating good presentation media. The results of the training show that there was an increase in students' knowledge after the training and before the training, as well as an improvement in skills assessed from several aspects, namely visual design, layout, use of visual elements, visual communication effectiveness, and group coordination and collaboration.